P495 Spacing the administration interval of anti-TNF agents: a valid strategy for patients with inflammatory bowel disease?. (25th January 2019) - Torres, P; Núñez, L; Aguilar, A; Mañosa, M; Mesonero, F; Cañete, F; Calafat, M; Fernandez, C; Cabré, E; López-Sanromán, A; Domènech, E
Abstract: Background: Patients with psoriasis and rheumatologic diseases are eventually treated with biological agents using treatment schedules with more spaced administrations than those approved. These schedules are cheaper and they even might reduce the risk of adverse events. However, these treatment strategies are scarcely used in inflammatory bowel disease (IBD). Methods: Aim: Two evaluate the clinical course of IBD patients treated with anti-TNF agents by means of a spacing strategy (administration interval greater than 8 weeks for infliximab or 2 weeks for adalimumab). Using the local databases from two referral centres, all the patients with IBD who were treated with infliximab or adalimumab by means of a spacing strategy, were identified. Patients with ostomy or ileoanal pouch, indication of anti-TNF therapy for perianal disease, or adverse events as the main cause for spacing strategy, were excluded. The spacing strategy success was considered if at the end of the follow-up the patient remained in clinical remission with the same spaced schedule or without biological therapy and if no return to the conventional schedule, dose-escalation, switch, swap, a course of systemic corticosteroids or surgery were required. Results: Eighty-five patients were included (58 Crohn's disease, 27 ulcerative/IBD unclassified). Sixty were treated with infliximab (49 every 10 weeks and 11 every 12 weeks) and 25 patients with adalimumab every 3 weeks. Prior to the index course of anti-TNF, 38% of patients followed a previous course of anti-TNF, and 7% required dose-escalation. The spacing schedule was initiated after the median of 25 months of anti-TNF treatment (IQR 14–49). Thirty-seven per cent had ileocolonoscopy (3% with endoscopic activity) and 17% MRI enterography (29% with RM activity) within 6 months before spacing began. 60% of patients were on concomitant immunomodulatory treatment at the beginning of spacing. The median time on spacing schedule was 15 months (IQR 12–25). Thirty-seven per cent of patients returned to a conventional schedule and 9% required dose-escalation. In 22 patients (26%) the anti-TNF was stopped because of sustained remission (9/22), clinical relapse (3/22), adverse events (2/22) or for other reasons (3 pregnancy, 3 neoplasia, 2 other). At the end of follow-up, 50 out of 85 patients (59%) met the success criteria of the spacing strategy. No baseline characteristics were found to be associated with success. Conclusions: Anti-TNF administration at longer intervals than the ones provided in the data sheet of the drug can be a convenient, safe, useful and cheaper alternative for IBD patients, even though, at this time, we do not have predictors of success.